Development of Aromatic Glutinous Rice for Rainfed Lowland Areas by Marker Assisted Selection - ,Srisawat Khanthong (Science Faculty of Chiang Mai University, 2019)
Glutinous rice is important in producing glutinous rice flour, festival foods, desserts and staple food in Southeast Asia regions. However, this rice crop is cultivated under rainfed condition. Blast disease and flash flooding which are major constraints in the production areas. Therefore, breeding rice with resistance to blast disease and tolerance to submergence are needed to maintain rice production. Marker assisted and stringent plant type selections (MAS and PTS) were employed to develop new glutinous rice genotypes with supreme cooking quality, high level of blast resistance and submergence tolerance by crossing RGD334-3-11-1-2-34 and RGD07334-34-16. MAS and PTS were carried out in F2 to F4 generations. Foreground selection for genes/QTL namely wx, badh2, SUB1, qBL1 and qBL11 was performed using gene specific and tightly linked markers. Twenty one superior F4 plants with combinations of five desirable traits including glutinous, blast resistance, submergence tolerance and grain aroma were selected and advanced to F5 generation. Phenotypic evaluation revealed that all F5 lines are glutinous having high level of blast resistance, outstanding submergence tolerance and strong grain aroma. This study confirmed that conventional and marker assisted selection approaches are effective in providing opportunities for breeders to pyramid genes/QTL in developing better rice cultivars.